An Overview of Gender Dysphoria: Factors, Effects, Treatments, and Islamic Perspective - Damri, Rafi; Wida, Aisyah Qonita Putri; Fuadhilah, Halda Afifa El; Uyun, Qurotul (Asian Journal of Islamic Psychology, 2024)
Gender dysphoria refers to the experience of a significant incongruence between an individual's assigned biological sex and their identified gender. Various disciplines, including medical, psychological, and religious perspectives, provide differing explanations for this condition. This article aims to explore the issue of gender dysphoria, examining its causal factors and the Islamic perspective through a comprehensive review of existing literature. According to the literature, the causes of gender dysphoria require further in-depth investigation. Researchers suggest that dysphoric behaviour arises from a complex interplay of psychological and biological factors. Interventions for gender dysphoria may include hormonal treatments and psychological support. Additionally, individuals with gender dysphoria often face impacts and comorbidities related to body image, anxiety, and other mental health concerns. From an Islamic viewpoint, gender dysphoria is considered to contradict the natural order (fitrah) and should be addressed to restore the individual's innate disposition (fitrah).